PERBEDAAN PENGETAHUAN DAN KADAR GLUKOSA DARAH PUASA SEBELUM DAN SESUDAH EDUKASI GIZI PADA PASIEN DM TIPE II DI RSU WISMA PRASHANTI TABANAN - Ni Wayan Sukiasih; Badrut Tamam; I wayan Juniarsana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2023)
Nutrition education is a form of nutritional intervention that aims to increase knowledge that can change behavior and compliance in undergoing a Diabetes Mellitus diet. The purpose of this study was to determine the effect of nutrition education on the level of knowledge and fasting blood glucose levels in type II DM patients at RSU Wisma Prashanti Tabanan. The type of research is pre-experimental with one group pretest and posttest design. Respondents in this study were 47 people with type II DM with purposive sampling technique. Nutrition education is to provide knowledge about good and correct eating patterns including dietary principles, dietary goals, dietary requirements, recommended and not recommended foods for ten minutes using leaflet media. Data analysis using Wilxocon test. The results  was: The nutritional knowledge of DM patients in the outpatient polyclinic of RSU Wisma Prashanti Tabanan General, the average score of 74.60 before being given nutrition education increased to 86.70 after being given nutritional education. The fasting blood glucose of DM patients in the outpatient clinic of RSU Wisma Prashanti Tabanan before being given nutrition education was 166.98 mg/dl decreased to 146.38 mg/dl after being given nutrition education. There was a difference in knowledge before and after nutrition education for DM patients at the poly Outpatient RSU Wisma Prashanti Tabanan  obtained p value = 0.000 (p (0.05). There is a difference in blood glucose levels before and after nutrition education in DM patients  RSU Wisma Prashanti Tabanan obtained p value = 0.009 ( p (0.05)Keywords: Blood Sugar Levels, Knowledge and Nutrition Education, Diabetes Mellitus